Development And Evaluation Of Nutribite Crackers Using Lotus Root (Nelumbium Nelumbo) (Journal of Food and Dietetics Research, 2024)
With increasing nutritional awareness among consumers, the value addition of snacks is gaining importance. The development and availability of value-added, nutridense snacks encourage consumers to make healthy snack choices. Value-added and nutridense snacks consumed by school-going children can contribute to a significant source of energy and nutrients. Lotus root is a less utilized vegetable containing various nutrients. It is a rich source of polyphenols, antioxidants, and dietary fiber. Lotus root is a versatile, culinary delicacy that can be cooked in different ways by stir-frying, boiling, braising, steaming, or deep-frying. This investigation was undertaken to develop a value-added, nutritious Nutribite Crackers, crispy textured and attractive lotus root-based snack for all age groups, especially pre-school and school children. Regular maize flour-based crackers were prepared and standardized as a control sample (MFC). Nutribite Crackers in three different variations (V-1, V-2, and V-3) were prepared using a combination of Lotus root, Maize flour, Wheat flour, Bajra flour, and Jowar flour. The developed crackers (Control: MFC and Variations: V-1, V-2, and V-3) were subjected to sensory evaluation, using a 9-point hedonic rating scale, to study the acceptability by 50 semi-trained panelists. Sensory evaluation results revealed that Nutribite Crackers prepared using Wheat flour, Maize flour, and Lotus root (V-1) were found to be most acceptable with total mean score of (52.02) out of (54), followed by (V-2) prepared using Jowar flour with a total mean score of (49.92) out of (54), then followed by (V-3) prepared using Bajra flour with total mean score of (47.84) out of (54). 100 g of best-rated Nutribite Crackers (V-1) has 545.85 kcal, 4.93 % crude protein, 20.37 % crude fat, 69.80 % carbohydrate, 1621.00 mg/kg potassium, 380.78 mg/kg calcium and 46.77 mg/kg iron. Control and all three variations showed a shelf life of more than 30 days under normal storage conditions. Lotus root incorporated Nutribite crackers (V-1) developed and standardized in this investigation serve as an ideal snack with several health-promoting nutrients for consumers.
Keywords: Lotus root; Wheat flour; Maize flour; Healthy snack; Value addition; Nutridense